MEMAHAMI GAYA BELAJAR UNTUK MENINGKATKAN POTENSI ANAK - Fenty Zahara Nasution; Elvira Elvira (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
One of the learning characteristics related to absorbing, processing, and conveying this information is the learning style of students. Learning style is a very important learning modality. Information related to the characteristics of the learning styles of students to be taught is very important for lecturers to improve the quality of their learning. Students will also find it easier to motivate themselves in learning. There are 3 learning styles such as visual, audio and kinesthetic where each style gives characteristics to the child. , the task of parents is to observe the child and then learn how to deal with the pattern of educating him at home. When students face obstacles from learning, it is necessary for the role of parents to know the child's learning style in order to help identify and develop the potential in each child. Some parents of students do a checklist about each child's learning style so that in understanding the parents can help so that the learning style becomes potential for the child